Role of routine blood tests for predicting clinical outcomes in osteosarcoma patients. (25th March 2019) - Jettoo, P; Tan, GJS; Gerrand, CH; Rankin, KS
Background: This retrospective cohort study aimed to investigate whether simple routine blood tests at presentation (C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), alkaline phosphatase and albumin) predict survival in patients with osteosarcoma. Methods: Between January 1998 and February 2015, 134 patients with a histological diagnosis of osteosarcoma were treated in our unit. Of these, 79 patients with high-grade osteosarcomas were included in the study. Demographic and clinical data, and laboratory parameters obtained prior to biopsy (CRP, ESR, alkaline phosphatase and albumin levels), were obtained from patients' records. Results: There were 44 males and 35 females. Univariate analysis showed that high pre-biopsy CRP ( p = 0.004), raised pre-biopsy ESR ( p = 0.010), older age ( p < 0.001), poor tumour necrosis rates (≤90%, p = 0.023) and metastasis at presentation ( p < 0.001) were poor prognostic factors. Multivariate analysis showed pre-biopsy CRP and ESR levels to be independent predictors of overall survival ( p = 0.020 and p = 0.025, respectively). Kaplan–Meier survival was significantly lower in patients with elevated CRP ( p = 0.002) and ESR ( p = 0.003). Hypoalbuminaemia and elevated alkaline phosphatase levels did not correlate with overall survival. Conclusion: Preoperative CRP and ESR levels may have value in building a prognostic model for patients presenting with osteosarcoma.